Overexpression of CDCA8 Predicts Poor Prognosis and Promotes Tumor Cell Growth in Prostate Cancer - Wan, Shun; He, Yang; Zhang, Bin; Yang, Zhi; Du, Fang-Ming; Zhang, Chun-Peng; Fu, Yu-Qiang; Mi, Jun (Frontiers in Oncology, 2022)
Human cell division cycle-related protein 8 (CDCA8) is an essential component of the vertebrate chromosomal passenger complex (CPC), which has confirmed that CDCA8 may play a role in promoting malignant tumor progression. However, the exact function of CDCA8 in the development and progression of prostate cancer (PCa) remains unclear. In this study, the database GSE69223 was downloaded by the gene expression omnibus (GEO) database, as well as CDCA8 expression differences in multiple tumor tissues and normal tissues were detected by the thecancergenomeatlas (TCGA), TIMER, Oncomine, and Ualcan databases. Kaplan-Meier and Cox regression methods were used to analyze the correlation between CDCA8 expression and prognosis in PCa. We also analyzed the association of CDCA8 expression with PCa clinical in the TCGA database. We confirmed the expression of CDCA8 in PCa tissues by The Human Protein Tissue Atlas (HPA). To further understand the role of CDCA8 in PCa, we assessed the effects of CDCA8 on PCa cell growth, proliferation, migration using the following methods in vitro studies. As a result, CDCA8 was significantly overexpressed in PCa cells compared with normal prostate cells. High CDCA8 expression predicts poor prognosis in PCa patients. In addition, CDCA8 expression was higher in high-grade PCa. Finally, overexpression of CDCA8 promoted PCa cell proliferation and inhibited apoptosis, and silencing of CDCA8 significantly inhibited PCa cell proliferation and migration. In summary, CDCA8 promoted the proliferation, migration, and healing of PCa cells.